Acoustic performance of embedded gypsum panels with cellulose fibers - Carvalho Araujo, Samique Kyene de [UNESP]; Oliveira, Diego Rodrigues de [UNESP]; Silva, Tiago Jose da [UNESP]; Barbosa, Juliana Cortez [UNESP]; Gava, Maristela (Univ Federal Santa Maria, 2016)
Currently, with the rationalization of consumption of raw materials due to energy constraints and possible damage to the environment, it has tried to maximize their employability. The forestry - wood sector is largely responsible for the generation of waste, which must be allocated appropriately to not lead to environmental damage. Thus, this study aimed to evaluate the acoustical panels made of plaster embedded with cellulose fibers from a pulp and paper company of the Paulista West. The evaluation was made based on the sound absorption material, resulting in sound absorption coefficients at around X, according to values found in literature.
Keywords: Sound absorption coefficient; Cellulose fibers; Plaster; Panel